Cyanine mitochondrial dye with slightly selective cytotoxicity against A549 cancerous cells. Issue 3 (27th November 2020) - Skvortsov, Dmitry A.; Emashova, Sophia K.; Kalinina, Marina A.; Dontsova, Olga A.
Abstract: Delocalized lipophilic cations (DLCs) are known as mitochondria‐addressed molecules. Mitochondria targeting may provide opportunities for tumor detection. DLCs may have antioxidant or anticancer properties. In this study, we focused on the toxicity and localization of 2‐[( E )‐2‐(5‐fluoro‐2‐methyl‐1 H ‐indol‐3‐yl)ethenyl]‐1, 6‐dimethylpyridin‐1‐ium iodide (62E2), which has recently been found as a novel cytotoxic fluorescent compound. The excitation maximum of 62E2 is 452 ± 10 nm and its emission maximum is 579 ± 10 nm. It is accumulated in the cells and stains mitochondria in nanomolar concentrations. 62E2 is cytotoxic and mitotoxic in low micromolar concentrations, and it demonstrates some selectivity of cytotoxicity against A549 cancer cells. The closest analog of 62E2 is F16, which is the fluorescent mitotoxic agent that has been described earlier as a potential anticancer agent. We hope that 62E2 described here is useful in expanding the diversity of cyanine fluorescent mitochondrial dyes and the analysis of their structure–activity relationships. Abstract : Compound 62E2 is a fluorophore with an excitation maximum at 452 ± 10 nm and emission at 500–600 nm, with an intensity maximum at 579 ± 10 nm. It is accumulated in cells and stains mitochondria in nanomolar concentrations. It demonstrates slightly selective cytotoxicity against the cancer cell line A549, in comparison with VA13 fibroblasts, and causes mitochondrial morphology changes in low micromolar concentrations.